Text on back: "Portrait de Largillère, acheté 85 rue Haxo Dimanche 5 avril 1885. Vois L'Insurge par Jules Valbr." From album 23
Text on back: "Portrait de Largillère, acheté 85 rue Haxo Dimanche 5 avril 1885. Vois L'Insurge par Jules Valbr." From album 23.